PENERAPAN METODE DEMONSTRASI BERBASIS KONTEKSTUAL PADA PEMBELAJARAN BIDANG STUDI FIQIH SISWA KELAS VII DI MTS SALAFIYAH SYAFI’IYAH SEBLAK JOMBANG - Farhan Harisuddin; Asriana Kibtiyah (JURNAL ILMIAH NUSANTARA, 2025)
In the world of education, the roles of educators and learners are inseparable. A teacher is someone who frequently interacts with students and delivers instructional material, which they are expected to master. Therefore, it is essential to employ appropriate approaches, media, and teaching methods that are suitable and well-received by the students. This research focuses on the implementation of the demonstration method and the inhibiting factors in its application at MTs. Salafiyah Syafi’iyah Seblak Jombang. The objectives of this study are as follows: 1) To examine the implementation of the context-based demonstration method in teaching fiqh to the students of MTs Salafiyah Syafi’iyah Seblak Jombang. 2) To identify the inhibiting factors in the implementation of the context-based demonstration method in teaching fiqh to the students of MTs. Salafiyah Syafi’iyah Seblak Jombang. This study aims to describe the implementation of the context-based demonstration method in the teaching of fiqh for seventh grade students at MTs. Salafiyah Syafi’iyah Seblak Jombang. The results of this research are expected to provide a positive contribution regarding the use of the demonstration method in the learning process.The approach used in this study is a qualitative approach, involving observation, interviews, and documentation. The data were analyzed using descriptive data analysis. The results of the study show that: 1) The fiqh teacher at MTs. Salafiyah Syafi’iyah Seblak successfully implemented the demonstration method through a cooperative learning strategy of the "think-pair-share" type, where students were divided into small groups and shared responsibility for helping peers who had not yet understood the material. 2) The inhibiting factors in the implementation of the demonstration method by the teacher during the learning process include: varying student abilities and students’ psychological/mental factors.